The Role of Principal and Teacher Leadership to Improve the Quality of Learning in SMA Negeri 5 OKU - Matsna Ahya; Syarwani Ahmad; Yessi Fitriani (research, training and philanthropy institution Natural Aceh, 2021)
This study aims to see the role of principals and teachers in improving the quality of learning at SMA Negeri 5 Ogan Komering Ulu (OKU). The formulation of the problem in this study is how the role of principal leadership and teacher professionalism in an effort to improve the quality of learning. This research is a qualitative research with a qualitative descriptive method. The data source is 50 teachers. The data technique is done by interview, observation and documentation. The results of this study illustrate that the role of principal ownership and teacher professionalism in an effort to improve the quality of learning in schools has been done as well as possible. This is with the shared role of the teacher in planning the Learning Implementation Plan that has been made and approved by the principal.